2001
DOI: 10.1161/hc3301.092790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Cyclooxygenase-2 Inhibition on Vascular Responses and Thrombosis in Canine Coronary Arteries

Abstract: Background Prostanoid synthesis via the action of cyclooxygenase-2 (COX-2) is a component of the inflammatory response. Prostacyclin, a product of COX-2 in vascular endothelium, has important physiological roles, such as increasing blood flow to injured tissues, reducing leukocyte adherence, and inhibiting platelet aggregation. We examined the possibility that selective COX-2 inhibition could suppress the protective effects of prostacyclin, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
96
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(109 citation statements)
references
References 25 publications
10
96
2
1
Order By: Relevance
“…COX2 is constitutively expressed in several locations in the kidney, including the loop of Henle, renal arterioles, and the macula densa, and undergoes inducible expression during inflammation (25,26). Intrarenal COX2 expression is important in the context of diabetes because its expression is augmented in the renal cortex of rats with streptozotocin-induced diabetes, largely due to the effect of hyperglycemia (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…COX2 is constitutively expressed in several locations in the kidney, including the loop of Henle, renal arterioles, and the macula densa, and undergoes inducible expression during inflammation (25,26). Intrarenal COX2 expression is important in the context of diabetes because its expression is augmented in the renal cortex of rats with streptozotocin-induced diabetes, largely due to the effect of hyperglycemia (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, NSAIDs may induce gastrointestinal injury [4,5,35], renal failure [7,25,34], and inhibit platelet aggregation [15,17] by several mechanisms. These side effects are correlated with the length of administration and dose of medication.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are in general mediated by the inhibition of inflammatory cyclooxygenase (COX-2). COX-2 is activated in injured tissue and produces prostaglandins (PGs) for hyperalgesia by sensitizing sensory nerve endings to various other mediators such as bradykinin, histamine and substance P. However, most NSAIDs also have various adverse effects including gastrointestinal irritation in dogs [4,5,35], renal disorders in dogs and rats [7,25,34], and inhibition of platelet aggregation in dogs [15,17] caused by the suppression of homeostatic cyclooxygenase (COX-1), which produces PGs for physiological roles within these tissues and cells [30]. Hepatotoxicity has also been reported after the administration of some NSAIDs in dogs [2,21,23].…”
mentioning
confidence: 99%
“…In two small trials with healthy human volunteers, the effects of aspirin were found not to be attenuated by celecoxib (15,16); however, in both trials, the volunteers were given a 324 mg daily dose of aspirin, which is four times the dose of 81 mg commonly considered to be "low-dose" aspirin. In a potentially related study, celecoxib did attenuate aspirin inhibition in a dog model of thrombosis (20).…”
mentioning
confidence: 91%